2000
DOI: 10.1073/pnas.97.9.4683
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal spermatogenesis and reduced fertility in transition nuclear protein 1-deficient mice

Abstract: Transition nuclear proteins (TPs), the major proteins found in chromatin of condensing spermatids, are believed to be important for histone displacement and chromatin condensation during mammalian spermatogenesis. We generated mice lacking the major TP, TP1, by targeted deletion of the Tnp1 gene in mouse embryonic stem cells. Surprisingly, testis weights and sperm production were normal in the mutant mice, and only subtle abnormalities were observed in sperm morphology. Electron microscopy revealed large rod-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
213
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(229 citation statements)
references
References 34 publications
12
213
2
2
Order By: Relevance
“…Indeed, the formation of a mature, compacted sperm nucleus (characterized by the replacement of nuclear histones with transition proteins and then protamines) and the development of the sperm flagellum, both originate during spermiogenesis. Moreover, experimental studies have demonstrated that targeted disruption of nuclear chromatin compaction (using protamine or transition protein insufficiency models) is associated with the development of an abnormal flagellum and defective motility [16,36]. Another potential explanation for the observed association between DNA integrity and motility lies in the inherent susceptibility of human spermatozoa to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the formation of a mature, compacted sperm nucleus (characterized by the replacement of nuclear histones with transition proteins and then protamines) and the development of the sperm flagellum, both originate during spermiogenesis. Moreover, experimental studies have demonstrated that targeted disruption of nuclear chromatin compaction (using protamine or transition protein insufficiency models) is associated with the development of an abnormal flagellum and defective motility [16,36]. Another potential explanation for the observed association between DNA integrity and motility lies in the inherent susceptibility of human spermatozoa to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…High frequencies of abnormal sperm are typical of mutants (Yu et al 2000;Lamitina & L'Hernault 2002;Mendoza-Lujambo et al 2002), although other factors may also contribute to the presence of abnormal sperm (Bakst & Cecil 1997). We found low levels of sperm abnormality among barn swallows from the control area, but elevated levels around Chernobyl.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression patterns of all postmeiotic genes examined, such as Tp1 (transition protein 1), Tp2 (transition protein 2), Prm2 (protamine 2), Gapdhs (glyceraldehyde 3-phosphate dehydrogenase-S, testis specific), Trf2 (TBP-related factor 2), and Crem (cyclic AMP-responsive element modulator) were comparable in Cib1 ϩ/ϩ and Cib1 Ϫ/Ϫ mice ( Fig. 4A; Tp1 and Gapdhs are not shown) (1,41,47,49). This is in sharp contrast to Crem knockout or mutant mice and Trf2 knockout mice, which have marked defects during the round spermatid stages and altered expression of the aforementioned genes (3,20,28,41,49).…”
Section: Male Cib1mentioning
confidence: 99%